Karakteristik Pemikiran Filosofis: Dampaknya Terhadap Pengetahuan Dan Peradaban Manusia - Husin, Ahmad; Olis (STAI Kuala Kapuas, 2025)
This article describes the characteristics and patterns of philosophical thought that underpin the development of human knowledge and understanding. Philosophy, as a discipline, has made significant contributions to exploring fundamental questions about existence, knowledge, ethics, and reality. In this journal, we analyze the main characteristics of philosophical thought and identify fundamental patterns that emerge in the evolution of philosophical thinking. This study is based on a comprehensive literature review involving major philosophical works from various historical periods. We identify several key characteristics of philosophical thought, including the diversity of concepts and theories, analytical and critical approaches, and efforts to achieve a deeper understanding of human and universal phenomena. Additionally, we uncover common patterns of philosophical thinking. These patterns involve the foundations of metaphysics and epistemology, questions about reason and experience, as well as reflections on ethics and goodness. These patterns have appeared throughout the history of philosophy in various schools of thought and traditions and continue to evolve over time. The findings of this study provide a better understanding of the process of philosophical thinking and how philosophy continues to contribute to human knowledge. By understanding the characteristics and patterns of philosophical thought, we can better appreciate the importance of philosophy in shaping human thought and civilization.